PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DI SMK NEGERI 1 BENAKAT - Nanda Elpita Sari; Depi Pramika; M. Totib M. Totib (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
Given the importance of entrepreneurial knowledge and the family environment as supporting factors in growing interest in entrepreneurship, it is hoped that after graduating from school students can participate in the country's economic development by creating jobs to reduce unemployment. This study wants to find out whether there is an influence of entrepreneurial knowledge and family environment on the interest in entrepreneurship at SMKN 1 Benakat. This research method is a quantitative research through multiple regression analysis with a questionnaire instrument, as well as documentation. The t-test results show that the entrepreneurial knowledge variable on the interest in entrepreneurship has an impact of 15%. The results of the t-test show that thefamily environment on the interest in entrepreneurship has an impact of 14%. Meanwhile, the F-test simultaneously shows the magnitude of the impact of 32%, so that information can be obtained that knowledge of entrepreneurship and the family environment simultaneously has an influence on interest in entrepreneurship at SMK Negeri 1 Benakat.